PENGARUH TAHAPAN PROSES PELUBANGAN DAN ARAH SERAT TERHADAP KEKUATAN TARIK MATERIAL KOMPOSIT POLYESTER-PANDAN WANGI - Heri Sunardi; Achmad Zainuri; Agus Dwi Catur (Dinamika Teknik Mesin, 2013)
Almost all components, both metallic and non-metallic, experience the process of splicing (joining) with other components. Metal components can be welded, bolted and riveted. However, a special non metal materials such as composites, joining can not be done by welding. One type of connection is suitable for composite materials and keeling bolt connection.             The purpose of this study was to investigate the influence of the stage of making a hole with drilling machine and a variation of the fiber direction tensile strength of fiber-reinforced composite material with at pandan wangi polyester matrix. On stage perforation process conducted by three stages with the first stage (diameter 2, then continued with a diameter of 4 and 6 mm), stage II (diameter of 4 and then continued with a diameter of 6 mm), and stage III (diameter 6 mm). And for a variety of fiber direction using random fiber direction, the direction, and woven with 30% fiber volume fraction.              The results of this study showed an increase in tensile strength composite material fiber reinforced polyester-pandan wangi with unidirectional fiber orientation, which contained the highest tensile strength of the composite stage I in the amount of 27.20 MPa and a tensile strength composite lowest was at stage III amounting 13:00 MPa. In a composite material with random fiber orientation tensile strength decreased by 19.93% with the highest tensile strength found in stage I in the amount of 17.90 MPa and the lowest tensile strength found in stage III at 8:00 MPa. And the orientation of the woven fiber tensile strength decreased by 51.09% with the highest tensile strength is found in the first stage of 17:30 MPa and the lowest tensile strength found in stage III at 6.80 MPa.